The peculiar life of Sundays - Miller, Stephen, 1941- (Harvard University Press, 2008)
From Augustine to Caesarius, through the Reformation and the Puritan flight from England, down through the ages to contemporary debates about Sunday worship, Miller explores the fascinating history of the Sabbath.